Hyperthermia induced oxidative damage in two wild caught African rodents, the diurnal four striped-field mouse Rhabdomys dilectus and the nocturnal Namaqua rock mouse Micaelamys namaquensis - Bennett, Nigel Charles (University of Pretoria, 2020)
Thesis (PhD (Zoology))--University of Pretoria, 2019.